EVALUATION OF RISK FACTORS OF PATIENTS WITH CHRONIC LOW BACK PAIN APPLYING TO THE PHYSICAL THERAPY AND REHABILITATION OUTPATIENT CLINIC - Barut, Ayşe Berhoğlu (International Journal of Research -GRANTHAALAYAH, 2021)
Objectives: To investigate the risk factors affecting these pains in patients with low back pain. Methods: In this retrospective observational study, the patients were asked about their age, gender, occupation, marital status, educational status, economic status and smoking status. The duration of low back pain was measured in months and the severity was 0-no pain and 10-unbearable pain on a 10 cm line with the Visual Analogue Scale (VAS) and the data were recorded. Results: Of 224 patients, 144 (64.3%) were female and 80 (35.7%) were male. The most common causes of chronic low back pain were lumbar spondylosis (120 patients, 53.6%) and discal hernia (68 patients, 30.4%). It was determined that the rate of low back pain was 72.3% higher in patients aged 60 and over. It was observed that as the education level increased, the rate of low back pain decreased significantly. 57.1% of the patients were found to be low-income; low back pain rate was higher in this group compared to the others. When we examined the relationship between smoking and low back pain, it was determined that 60.7% of the patients with low back pain were smoking. Conclusion: A significant relationship was found between low back pain and an advanced age female patient, low economic level, low education level, and smoking.